2011
DOI: 10.1136/bjsports-2011-090204
|View full text |Cite
|
Sign up to set email alerts
|

A randomised control trial of short term efficacy of in-shoe foot orthoses compared with a wait and see policy for anterior knee pain and the role of foot mobility

Abstract: ACTRN12611000492954.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 32 publications
10
106
0
3
Order By: Relevance
“…In contrast, greater usual pain was identified within one LQ study to be predictive of patellar taping success (mean 0.43, 95 % CI 0.01-0.85) [40]. The most significant limitation of these findings is that only immediate effects were assessed.…”
Section: Painmentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, greater usual pain was identified within one LQ study to be predictive of patellar taping success (mean 0.43, 95 % CI 0.01-0.85) [40]. The most significant limitation of these findings is that only immediate effects were assessed.…”
Section: Painmentioning
confidence: 90%
“…Vicenzino et al [19] reported a mid-foot width difference from non-weight-bearing to weight-bearing [10.96 mm significantly predicted success when a significance level of p \ 0.20 was used and in subsequent regression analysis. Similarly, Mills et al [40] reported a difference in mid-foot width of [11.25 mm correctly predicted orthoses success in 7 of 10 individuals using a classification tree model. Variability in clinical measures prevents direct comparison between prognostic and predictor studies; however, considering dynamic rearfoot eversion has been identified as a potential predictor of foot orthoses success [32], there is clear merit for further exploration of dynamic foot posture measures in predicting orthoses intervention outcomes.…”
Section: Foot and Anklementioning
confidence: 93%
See 2 more Smart Citations
“…In that study, foot mobility, as measured by the change in arch height between weight-bearing and non-weight-bearing, was four times more likely to be seen in individuals with patellofemoral pain compared to a control group [5]. Furthermore, Milles and associates reported that individuals with anterior knee pain who had increased midfoot mobility were more likely to experience a reduction in their symptoms when treated with pre-fabricated orthoses [6]. Foot hypermobility has also been associated with an increased risk of other injuries in sports, particularly the lower extremity [7].…”
Section: Introductionmentioning
confidence: 89%